1998
DOI: 10.1179/mst.1998.14.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of γ → α phase transformation in Fe-Mn alloys containing low manganese

Abstract: The kinetics of the Y--+ a phase transformation in Fe-Mn alloys with low Mn contents was studied using differential scanning calorimetry. Analysis of the measured heat capacity yielded both the austenite fractions as a function of temperature as well as the enthalpy difference between ferrite and austenite which decreases with increases in both the temperature and the Mn concentration.The transformation was modelled using an interface controlled growth model. It was assumed that the interface velocity is propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…where P α/γ is the effective driving pressure; M α/γ is the interfacial mobility of the moving α/γ interface, which can be described as [55]…”
Section: Ferrite Growth and Coarseningmentioning
confidence: 99%
“…where P α/γ is the effective driving pressure; M α/γ is the interfacial mobility of the moving α/γ interface, which can be described as [55]…”
Section: Ferrite Growth and Coarseningmentioning
confidence: 99%
“…A lot of effort has been placed to clarify the intrinsic mobility in various binary and ternary alloys. [4][5][6][7][8][9] It is clear that M int decreases with lowering temperature while the intrinsic mobilities reported in literature scatters by orders of magnitude. Recently intrinsic mobility is reported to be nearly independent on transformation direction, e.g.…”
Section: Intrinsic Mobilitymentioning
confidence: 92%
“…To take the finite interface mobility into account, the value of acicular γ/TM interface mobility is needed for the DICTRA calculation. Several α/γ interface mobilities were reported for fcc → bcc massive transformations [21][22][23]. The massive transformation occurs by migration of incoherent interface; therefore, the mobility of the acicular γ/TM interface with better coherency should be smaller than the reported mobilities.…”
Section: Dictra Simulation Of the Growth Of Austenitementioning
confidence: 92%
“…The massive transformation occurs by migration of incoherent interface; therefore, the mobility of the acicular γ/TM interface with better coherency should be smaller than the reported mobilities. Hence, in this study, in order to reduce the interface mobility, the reported interface mobility [21] (M 0 = −4 × 10 −7 exp(−140,000/RT) m 4 /Js) was multiplied by various small constants (1~0.001) to evaluate the growth of acicular γ, as simulated in the isothermal holding process [16].…”
Section: Dictra Simulation Of the Growth Of Austenitementioning
confidence: 99%